Strategic planning for higher performance : a fundamental approach - Ohaba, Jacob Ata (Zaria, Nigeria : Onis Excel, 2001)
The book addresses the task of mastering the complex processes involved in establishing achievable objectives, the wisdom of devising effective strategies and the practical steps in planning and implementing them.
Includes bibliographical references and index.
oif 05/11/14; 12/08/15
Loan
Keywords: Strategic planning; Organisational effectiveness; Performance -- Management